An orbital and electron density analysis of weak interactions in ethanol-water, methanol-water, ethanol and methanol small clusters (2012)
A computational study of (ethanol)n-water, n = 1 to 5 heteroclusters was carried out employing the B3LYP/6-31+G(d) approach. The molecular (MO) and atomic (AO) orbital analysis and the topological study of the electron density provided results that were successfully correlated. Results were compared with those obtained for (ethanol)n, (methanol)n, n = 1 to 6 clusters and (methanol)n-water, n = 1 to 5 heteroclusters. These systems showed the same trends observed in the (ethanol)n-water, n = 1 to 5 heteroclusters such as an O-O distance of 5 Å to which the O-H-O hydrogen bonds (HBs) can have significant influence on the constituent monomers. The HOMO of the hetero(clusters) is less stable than the HOMO of the isolated alcohol monomer as the hetero(cluster) size increases, that destabilization is higher for linear geometries than for cyclic geometries. Changes of the occupancy and energy of the AO are correlated with the strength of O-H-O and C-H-O HBs as well as with the proton donor and/or acceptor character of the involved molecules. In summary, the current MO and AO analysis provides alternative ways to characterize HBs. However, this analysis cannot be applied to the study of H-H interactions observed in the molecular graphs. © 2012 American Institute of Physics.